CONTROLLING PHOSPHATE RELEASE FROM PHOSPHATE-ENRICHED SEDIMENTS BY ADDING VARIOUS IRON COMPOUNDS - Smolders A.J.P.; Lamers L.P.M.; Moonen M.; Zwaga K.; Roelofs J.G.M. (My University, 2001)
In a laboratory experiment, different iron salts (FeCl2, FeCl3, FeSO4) and Fe2O3 were added to a phosphate enriched silty loam sediment in order to study their effect on phosphate mobilisation. Phosphate concentrations in sediment pore water were not reduced by the addition of Fe2O3. Addition of both iron chlorides, however, resulted in a strong decrease of phosphate levels in sediment pore water. A similar but less pronounced effect was caused by the addition of iron as iron(II) sulphate. Sulphate appears to counteract the immobilisation of phosphate brought about by iron(II). Phosphate release from the sediment appeared to be determined by the iron/phosphate ratio in the sediment pore water. The addition of Fe2O3 barely affected the phosphate release from the sediment whereas the addition of iron salts was effective in preventing phosphate release. Increased amounts of iron added to the sediment resulted in a decreased phosphate release.
Keywords: EUTROPHICATION; IRON CHEMICALS; IRON SPECIES; PHOSPHATE; PHOSPHORUS MANAGEMENT; SEDIMENT; SULPHATE